SITLA and Legislative Oversight—Wise Long-term Direction under Evolving Charitable Trust Duty, or Shortsighted Micromanagement? (Utah Environmental Law Review, 2009)
Imagine that your third-grader has to share a math text book because there are not enough to go around. Imagine your pristine state-owned undeveloped hillside view, for which you paid a premium, has become cluttered with backhoes and bulldozers. One or both scenarios may provoke outrage. Either circumstance frames this question: to what extent should the lands granted in trust for the benefit of the State’s school children be developed and consumed to support a public school system that ranks lowest in the nation for school funding per child? This is the dilemma facing Utah’s legislature as School and Institutional Trust Lands Administration (“SITLA”), Utah’s entity for managing school trust lands, engages in its fiduciary duties to its beneficiaries, the state’s school children.